Retraction notice to Thermal study on non-Newtonian fluids through a porous channel for turbine blades [Case Stud. Therm. Eng. 49 (2023) 103185] (Case Studies in Thermal Engineering (2023) 49, (S2214157X23004914), (10.1016/j.csite.2023.103185)) - Zhu C.-Z.; Nematipour M.; Bina R.; Fayaz H. (Elsevier Ltd, 2024)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/locate/withdrawalpolicy). This article has been retracted at the request of the Editor-in-Chief. In investigating concerns brought up regarding the authorship of the article, the editor reached out to the authors for an explanation. In addition to the concerns originally raised, the editor discovered suspicious changes in authorship between the original submission and the revised version of this paper. In summary, two (2) authors were removed, and three (3) authorsChao-zhe Zhu (new first author)